The protein inventory of Clostridium difficile grown in complex and minimal medium. Issue 9 (12th September 2016) - Otto, Andreas; Maaß, Sandra; Lassek, Christian; Becher, Dörte; Hecker, Michael; Riedel, Katharina; Sievers, Susanne
Abstract : The intestinal pathogen Clostridium difficile is causing an increasing number of infections often characterized by severity and high relapse rates. Profound knowledge of the physiology of the pathogen could help to develop new treatment strategies. Proteomics, a valuable tool to study bacterial physiology, was used in this work to establish a benchmark proteome of reference strain C. difficile 630Δ erm with MS‐based details on all identified proteins. Our elaborate annotation and visualization of C. difficile 630Δ erm 3764 ORFs will serve as a valuable base for researchers having to evaluate global expression studies. To exemplify expression variability, protein expression of late exponentially growing cells in complex brain–heart infusion medium and C. difficile minimal medium was compared. Noteworthy results of this comparison are as follows: (i) the higher expression of enzymes for the biosynthesis of some vitamins and purine and (ii) downregulation of proteins involved in butanoate fermentation in C. difficile minimal medium. However, the abundance of proteins involved in DNA metabolism, protein synthesis, and the cell envelope showed no variation between the two growth media.